Expert systems! Who knows? - Vestergaard, Flemming (Psyke & Logos, 2023)
A number of aspects of knowledge representation in expert systems are discussed. The aim is mainly to introduce to them, and as regards expert system technology the discussion is quite introductory, the perspective being more that of simple practice in the field than state-of-the-art applications. The main subject is how knowledge is embodied in expert systems, in particular with respect to explicitness and articulation. It is suggested that expert systems may embody knowledge in ways more similar to human knowledge representation than do conventional computer systems. Important reservations concerning this claim are also made.